2005
DOI: 10.1002/jemt.20168
|View full text |Cite
|
Sign up to set email alerts
|

Perovskites in the comb roof base of hornets: Their possible function

Abstract: On the ceiling of the Oriental hornet comb cell, there are mineral granules of polycrystalline material known to belong to the group of perovskites. In a comb cell intended to house a worker hornet, the roof base usually carries one or several such perovskite granules containing titanium (Ti), whereas in the roof base of a cell housing a developing queen, there are usually several granules containing a high percentage of silicon (Si), aluminum (Al), calcium (Ca), and iron (Fe), but very little if any Ti. In wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Inspection of these heavy-element particles at the SE mode, at either zero tilt or high-angle 70°tilt, enabled to reveal the intrinsic nature of these particles, i.e., that they were well embedded in the comb structure, possibly covered by an organic layer, which prevented the detection of EBSD signals from most regions of the particles. The relative percentage of each of the elements in the mineral has been previously presented in detail (Stokroos et al 2001;Ishay et al 2005b). In the present study, however, we focused on and sought mainly Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspection of these heavy-element particles at the SE mode, at either zero tilt or high-angle 70°tilt, enabled to reveal the intrinsic nature of these particles, i.e., that they were well embedded in the comb structure, possibly covered by an organic layer, which prevented the detection of EBSD signals from most regions of the particles. The relative percentage of each of the elements in the mineral has been previously presented in detail (Stokroos et al 2001;Ishay et al 2005b). In the present study, however, we focused on and sought mainly Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was suggested that a perovskite phase may be the origin of the titanium-containing particles (Stokroos et al 2001;Ishay et al 2005b). Although main emphasis was given to the ilmenite, likewise identified by X-ray diffraction, the FeSiO 3 phase was also considered.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the recognized use of titanium minerals by extant organisms is rare and may result from collection of titanium-containing minerals from the environment, rather than “biotitanification.” Recent research suggests, however, that titanium minerals may have played a role in the origins of life …”
Section: Introductionmentioning
confidence: 99%